2002
DOI: 10.1136/oem.59.5.329
|View full text |Cite
|
Sign up to set email alerts
|

Stomach cancer and occupation in Sweden: 1971–89

Abstract: Objectives: To examine the relation between gastric cancer and occupation among men and women gainfully employed in 1970 in Sweden for the period 1971-89 and, more specifically, to evaluate whether any excess of incidence of gastric cancer had also occurred among the subcohort of people reporting the same occupation in 1960 and 1970. Methods: In both sexes and cohorts, relative risks adjusted for age, period of diagnosis, and geographical risk area were computed for occupational codes specified at one, two, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…12 This is in line with the results of the current study. However, no association between specific exposure to organic solvents and risk of gastric cancer was found in a Swedish case-control study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…12 This is in line with the results of the current study. However, no association between specific exposure to organic solvents and risk of gastric cancer was found in a Swedish case-control study.…”
Section: Discussionsupporting
confidence: 92%
“…23 There have been reports on positive associations between various occupational groups and risk of gastric cancer, 10,12 notably ''dusty'' occupations, e.g., coal and tin mining, [24][25][26][27][28][29] metal processing, [30][31][32][33][34][35] rubber manufacturing [36][37][38][39][40] and carpentry or construction work. 10,12 Other dusty work environments have also been implicated in the etiology. [41][42][43][44] However, possible occupational exposures linked to a risk of gastric cancer have not been established, since the majority of previous studies have not addressed specific exposures, have not adjusted for potential confounders, or have revealed only weak associations without dose-response patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food industry workers as an undivided occupational group have shown an elevated risk of cancer of the oesophagus, 11 stomach, [12][13][14] small intestine, 15 gall bladder 16 and pancreas. 16 We only found an excess of pancreas cancer among Finnish male food industry workers.…”
Section: Discussionmentioning
confidence: 99%
“…studies showed that Pylori infection, smoking, and exposure to industrial materials such as nitrogen oxides, N-nitro compounds, and ionizing radiation are among the important factors of stomach cancer (Cocco et al, 1994;Forman and Burley, 2006;Hartgrink et al, 2009;Malekzadeh et al, 2009;Radmard, 2010;Hasanzadeh et al, 2013). Studies also have shown a higher incidence of stomach cancer in certain occupational groups, including miners and quarrymen, farmers, fishermen, masonry and concrete workers, machine operators, nurses, food industry workers, cooks, launderers, and dry cleaners (Swanson and Burns, 1995;Kang et al, 1997;Simpson et al, 1999;Aragonés et al, 2002).…”
Section: Spatial Analysis Of Stomach Cancer Incidence In Iranmentioning
confidence: 99%